Happy birthday, Babymouse! - Holm, Jennifer L. (Holm, Jennifer L. Babymouse, 2014)
Babymouse imagines the biggest, most wonderful birthday party ever for herself and tries to make it happen, but Felicia is planning her own birthday bash for the very same day.